(untitled) (Economic and Political Thought, 2017)
The article aims to answer the question that is nowadays often asked during scientific discussions and among politicians: Does the European Union endanger Poland and Poland’s national interests? Under the influence of criticism of globalisation and its negative effects as well as the mega-crisis, which the EU has not been able to overcome for a long time, populism and nationalistic tendencies are growing in Europe and in the world. As a result, extreme right wing parties glorifying the essence of a national state and negating the sense of the existence of the European Union, which cannot cope with the financial and economic crisis, migration, leadership, axiology, international terrorism and many other problems, come to power. Globalisation and the EU are deemed to be the sources of those problems, which many countries in Europe and in the world face. The article presents theoretical and practical aspects of the European Union specificity and its significance in international relations, especially for national states – exemplified by Poland – in the realities of the contemporary, dynamically changing world. The main thesis is a statement that the EU does not directly endanger a member state and its national interests. However, in some circumstances, for the benefit of the majority of its members, it may limit and limits its political sovereignty and international activeness. As a result, it makes a member state act in a way that is in conflict with its national interest and the reason of state.